2015
DOI: 10.1111/aos.12911
|View full text |Cite
|
Sign up to set email alerts
|

Sports‐related eye and adnexal injuries in the Western Australian paediatric population

Abstract: ABSTRACT.Purpose: To identify the causes of sports-related eye and adnexal injuries in children in Perth, Western Australia, to determine which sporting activities pose the highest risk of eye and adnexal injury to children. Methods: We performed a 12-year retrospective review of children admitted to hospital from 2002 to 2013 with sports-related ocular and adnexal eye injuries. The main outcome measures were the cause and type of ocular and adnexal injuries, age and gender risk factors. Results: A total of 93… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 20 publications
1
22
1
2
Order By: Relevance
“…Sports equipment was the major cause for eye injuries (15%) and the same has been observed in previous studies (Strahlman et al 1990;McEwen et al 1999;Hoskin et al 2016). Instead, in other Scandinavian countries airsoft pellet guns in Denmark (17.4%) and projectiles in Norway (21.5%) were the most common injury mechanism (Takvam & Midelfart 1993;Saunte & Saunte 2008).…”
Section: Discussionsupporting
confidence: 69%
“…Sports equipment was the major cause for eye injuries (15%) and the same has been observed in previous studies (Strahlman et al 1990;McEwen et al 1999;Hoskin et al 2016). Instead, in other Scandinavian countries airsoft pellet guns in Denmark (17.4%) and projectiles in Norway (21.5%) were the most common injury mechanism (Takvam & Midelfart 1993;Saunte & Saunte 2008).…”
Section: Discussionsupporting
confidence: 69%
“…One relatively simple approach is to advocate the use of suitable eye protection when engaging in potentially high-risk activities as has been advocated by several previous authors. 23 26 It is now mandatory for squash players <19 years of age to wear protective eyewear when playing in England squash tournaments. This is a beacon of best practice.…”
Section: Discussionmentioning
confidence: 99%
“…Corneal laceration, globe rupture and hyphaema are the most frequent eye injuries caused by fishhook, fishing lure or weights. In a study by Hoskin et al [7] fishing-related eye injuries were found in 7% of sport-related injuries in a Western Australian pediatric population.…”
Section: Case Reportmentioning
confidence: 96%